Mass Culture, Imports and Conspicuous Consumption - Annie Tubadji (Journal of Economic Issues, 2023)
This study investigates how a country’s promotion of its culture affects anothercountry’s consumption patterns. We collected primary data from Malaysians abouttheir exposure to Korean drama and consumption of Korean cosmetics in order to testwhether the imaging of Korean cultural richness through the international marketingstrategy termed Hallyu (entailing the use of Korean TV drama to image South Korea asa celebrated country) instigates conspicuous consumption in Malaysia. Respondents withhigher levels of education but lower income watched Korean drama more intensively, andthe intensity of watching Korean drama was positively associated with the consumptionof Korean cosmetics. Our results highlight the ability to affect trade between countries byadvertising through mass culture and exploiting the need for conspicuous consumption bythose individuals experiencing perceived relative deprivation